ChemInform Abstract: Thioetherification via Photoredox/Nickel Dual Catalysis. Issue 27 (16th June 2016) - Jouffroy, Matthieu; Kelly, Christopher B.; Molander, Gary A.
Abstract: The photoredox thioetherification of (hetero)aryl bromides (II) with thiolsilicate (I) leads to a variety of (hetero)aryl propyl thioethers (III).